Metabolic profiling of Meyerozyma guilliermondii strain SO and a recombinant strain SO2 expressing lipase - Fam, Jye Ping (2018)
A locally isolated yeast, Meyerozyma guilliermondii strain SO is capable of acting as a host to express heterologous protein under the regulation of methanol-dependence alcohol oxidase promoter (PAOX). Methanol is a potent compound to induce the PAOX. However, M. guilliermondii strain SO has shown its ability to express the bacterial recombinant thermostable lipase from Geobacillus zalihae strain T1 without methanol induction. Metabolite profiling could facilitate in understanding the distinctive compounds of the metabolic pathway in this system after the lipase was expressed. This study aims to investigate and identify the metabolites responsible for PAOX auto-induction in this newly developed expression system. Initially, the time point where the lipase was expressed optimally without methanol in Yeast extract-Peptone-Tryptic soy broth (YPT) medium was determined, followed by metabolites extraction. Then, the metabolites were detected using gas chromatography-mass spectrometry (GC-MS). A multivariate statistical analysis (MVA) was performed and biosynthetic pathways for the respective metabolites were determined from the KEGG database. The results showed that the optimum time for lipase expression without methanol was detected after 60 h cultivation with 3.34 U/mL activity. In contrast, no lipase activity was detected in the commercial system, Komagataella pastoris without methanol as the inducer. In this study, MVA namely principle component analysis (PCA) and partial least square discriminant analysis (PLS-DA) were used to determine the relationship between metabolites present in wild-type SO and recombinant strain SO2 carrying T1 lipase. Upon evaluation of four different samples at 0 and 60 h, numbers of primary metabolites such as fatty acids, amino acids and organic acids were significantly present based on the separation trend and the contribution of metabolites in PCA and PLS-DA. Further interpretation using variable importance in projection (VIP) scores of PLS-DA showed that eicosanebioic acid and benzeneacetic acid were the most significant compounds present in four different sets of intracellular and extracellular samples, respectively. In addition, the heatmap analysis and showed a slightly abundance of fatty acids (eicosanoic acid, eicosanebionic acid, octadecenoic acid and hexadecenoic acid) produced throughout the cultivation period. The pathway analysis showed the significant number of hits for fatty acid and unsaturated fatty acid biosynthesis from the compounds detected. Finally, using the available data, a biosynthetic pathway was reconstructed and the metabolites responsible for auto-induction of PAOX were found to be unsaturated fatty acids. In conclusion, metabolites of strain SO and its recombinant SO2 were successfully profiled and identified. This finding was significant where these unsaturated fatty acids could be used as the alternative inducers for PAOX in M. guilliermondii strain SO expression system.